2021
DOI: 10.1002/app.51377
|View full text |Cite
|
Sign up to set email alerts
|

Efficient cage structured polyhedral oligomeric silsesquioxane embedded poly(vinyl alcohol) membranes: Thermal degradation and mechanical stability in hydrated condition

Abstract: In this work, the thermal degradation of functionalized cage structured polyhedral oligomeric silsesquioxane (POSS) incorporated poly(vinyl alcohol) (PVA) and poly(vinyl alcohol)-poly (ethylene oxide) (PEO) blend membranes were discussed. PVA-PEO/POSS and cross-linked PVA/POSS systems exhibited excellent improvement in thermal stability at lower loading of POSS as compared to pure PVA and uncross-linked PVA/POSS system. Uncrosslinked PVA and PVA/POSS systems exhibited mainly two degradation steps. However, cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…48 The fourth stage was observed at a temperature above 400 °C (stage D) and involved the degradation of carbonaceous materials yielded in the former stages. 49 The addition of water greatly influenced the weight loss in the first stage, owing to the evaporation of water, whereas similar degradation behaviors were observed in the subsequent stages. This indicated that water could be removed in the first stage, thus exerting minimal influence on the intrinsic decomposition process of PVA.…”
Section: Thermal Analysis Of Pva Pelletsmentioning
confidence: 71%
See 1 more Smart Citation
“…48 The fourth stage was observed at a temperature above 400 °C (stage D) and involved the degradation of carbonaceous materials yielded in the former stages. 49 The addition of water greatly influenced the weight loss in the first stage, owing to the evaporation of water, whereas similar degradation behaviors were observed in the subsequent stages. This indicated that water could be removed in the first stage, thus exerting minimal influence on the intrinsic decomposition process of PVA.…”
Section: Thermal Analysis Of Pva Pelletsmentioning
confidence: 71%
“…The largest DTG peak in the range of 300–400 °C was related to the third stage (stage C), where chain scission of PVA molecules took place . The fourth stage was observed at a temperature above 400 °C (stage D) and involved the degradation of carbonaceous materials yielded in the former stages . The addition of water greatly influenced the weight loss in the first stage, owing to the evaporation of water, whereas similar degradation behaviors were observed in the subsequent stages.…”
Section: Resultsmentioning
confidence: 86%